Automatic motorcycle security mechanism using ATMEGA328 microcontroller iniegrated with RFID [electronic resource] - Muhammad Fakhri Mohd. Noh, 1992-; Tan, Chee Wei, supervisor (2015)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2015